Voluntary organizations and local governance - Mangada, Ladylyn L. (1998)
This study examined the receptivity of voluntary organizations to local governance. Drawing inspiration from perceptions that individuals/groups from poor, non-urban setting are reluctant to face new challenges in governance, the paper explored the issue in favor of the 4th to 6th class municipalities, in particular, those located in Easter/Western Samar and Leyte provinces. More specifically, the study aimed to examine the receptivity of voluntary organizations to local governance in terms of: a) their response to new challenges of governance, b) comparative advantages and disadvantages, and c) nature of interaction with the bureaucracy.
With the approval of the 1991 Local Government Code which opened opportunities for voluntary organizations to substantially participate in local governance, Leyte and Samar community-based organizations positively responded to this new challenge of actively assisting the local government units towards the development of autonomous and sustainable communities. They all shared the belief that having more people involved in development and making them stakeholders in the process is one sure way of ensuring that their plans will be implemented, monitored and its impact felt. As such most of them sit in a number of mandated and non-mandated special bodies and successfully dip their fingers into the rough-and tumble world of politics as konsehal and kapitan in their locality.
The results also revealed that with their participation, local government units has learned to treat voluntary groups not as mere beneficiaries but active partners in planning, monitoring, implementation, of projects and programs affecting their own lives. Thus, they should be nurtured, encouraged and activated methodically.
While they have shown eagerness in assuming responsibility as partners in local governance, insufficient resources and lack of skill, knowledge and experience in leadership and managerial capacities limit sustained and effective engagement with the government. Participatory lifestyle, positive relations with the beneficiaries, the culture of service of the people involved in volunteer work, and minimized red tape in its operations were identified as some of its dominant strength in co-governance.
Moreover, voluntary groups in Leyte and Samar interaction with local governance units have been short term both in tie and resources invested. Both parties exert effort to avoid duplication of activities to achieve efficiency in field operations. Such level of engagement maybe exploratory but generates familiarization and confidence-building. Although, not the ideal or preferred type of partnership, this is less objectionable to local government executives. Yet both actors should work toward a more progressive and mature partnership instead of being stuck in purely short time "consultative, coordinative, complementary" relations.
1998 G. E. Professorial Chair -- University of the Philippines, Tacloban.
Includes bibliographical references.
Keywords: Non-government organizations -- Philippines -- Eastern Visayas; Volunteer organizations -- Philippines -- Eastern Visayas; Local governance -- Philippines -- Eastern Visayas